Open science for nutrition and physical activity research: a new challenge and lots of opportunities for IJBNPA - Russell Jago; Hidde van der Ploeg (BMC, 2018)
Abstract Open science has received a great deal of attention across the academic community. Open science has been defined in many ways, but the central principle is to make methods, results and the underpinning data (publicly) available. The aim of this editorial is to outline the key issues that the nutrition and physical activity fields need to consider in relation to making the research within the field as transparent and reproducible as possible. We provide a brief overview of the key issues to consider and provide open science recommendations for publications within IJBNPA and the wider field.